A MODELLING RELATIONSHIP BETWEEN WORK SATISFACTION AND FACULTY PERFORMANCE IN THE NIGERIAN PRIVATE UNIVERSITIES - Adeniji, A. A.; Falola, H. O; Salau, O. P (European Scientific Journal, ESJ, 2014)
Given the pivotal role that academics play in determining the efficiency, effectiveness and sustainability of educational sector of the economy, coupled with the constant mobility of these highly skilled persons from one University to another, it is important to understand what motivates them, and the extent to which the University environment and other contextual variables affect their performances. Thus, the paper utilizes survey data collected from 558 faculties of selected private Universities in the Southwest Nigeria to find out the factors that will determine the work satisfaction of faculties and their impact on academic excellence, whether faculties leave based on their dissatisfaction with these factors. Structural Equation Model (SEM) was used to analyze the relationships between the dependent and the independent variables. The results showed close association between the tested variables. The study stood as an eye opener to the management to ensure that existing benefits for academic staff are fairly, justly and competitively allocated to them as this affect their level of commitment and overall performance. Thus, we concluded that salary, package, organizational policies, work condition, social context of the job, as it relates to academic autonomy, relationship with academic colleagues, participation in decision making, promotional opportunities, etc will have positive effects on faculty’s commitment to their academic activities and subsequently impact on their performances.